Bohdan Kistjakowski i jego doktryna państwa prawnego - Jędrysiak, Marcin (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2017)
The article concentrates on Ukrainian legal philosopher and sociologist – Bogdan Kistiyakovsky. Kistiyakovsky was the a famous and important theoretician of law and state. This work is an attempt to describe his approach to the idea of state and the concept of sovereignty of law.First part on the article serves the purpose of showing Kistiyakovsky as an important historical figure and to show why is it relevant to know and understand his works. Thus, this part of article focuses mostly on his biography and the general depiction of his works.After brief description of his early life, family and political or scientific activity, second part would concentrate on his neokantian methodology of social science – a very important factor in his works – and briefly describe his idea of law.The main part of this paper analyzes the general shape of his theory of state, the main point of which is the idea of state power. Then his vision of development of state regimes will be described. That would let to realizing the main goal of the paper: understanding of his theory of the state law and the common relations between the law and the state. The next part focuses on his vision of the constitutional state.Ending contains a summary with answers the main problems of the article: what are the important features of the state law and what idea might had inspired the Ukrainian thinker.
Keywords: Ukraina; Rosja; teoria państwa; praworządność; Kistiakovsky, Bohdan; Krabbe, Hugo; prawo